The characteristics of the elderly with hypertension in Jatimulyo Village - Mega Elvina Rosa; Bonita Suharto; Sri Sunaringsih Ika Wardojo (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Physical and psychological decline is a sign of aging. In addition, aging also increases the risk of diseases that can lead to death. Hypertension is a non-communicable but chronic disease with a very high prevalence rate in the elderly. Many changes occur during the aging process. These changes need special attention. In the elderly, some problems arise from physical, cognitive, social, and sexual feelings. One of the changes in the cardiovascular system in the elderly is hypertension. Methods: The samples used were ten patients according to the inclusion and exclusion criteria. The research data is primary data obtained from interviews based on questionnaires. Of the ten research subjects, the proportion of hypertension was found in problems with the characteristics of age 60-74 years as much as 70%, female gender (70%), high school education level (60%), and existing housewife occupation (70%). In addition, most of the research subjects had grade 1 hypertension (90%). Results: Of the ten research subjects, the proportion of hypertension was found in problems with the characteristics of age 60-74 years as much as 70%, female gender (70%), high school education level (60%), and housewife occupation (70%). In addition, most of the research subjects had grade 1 hypertension (90%). Conclusion: Hypertension is also a non-communicable but chronic disease with a very high prevalence rate in the elderly. The prevalence of hypertension at the world level, especially in developed countries, in the elderly population > 60 years is estimated to reach two-thirds or around 60%-80%.